2023
DOI: 10.1093/ecco-jcc/jjad152
|View full text |Cite
|
Sign up to set email alerts
|

Superior predictive value of transmural over endoscopic severity for colectomy risk in ulcerative colitis: a multicentre prospective cohort study

Nicole Piazza O Sed,
Daniele Noviello,
Elisabetta Filippi
et al.

Abstract: Background and Aims Endoscopic activity is associated with an increased risk of surgery in patients with ulcerative colitis (UC). Transmural activity, as defined by Milan Ultrasound Criteria (MUC) >6.2, reliably detects endoscopic activity in patients with UC. The study aimed to assess in UC patients whether transmural severity is a better predictor of colectomy as compared to endoscopy. Methods Consecutive adult UC pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Notably, MUC, over EMS and even BWT, was the only significant predictor of Cox proportional hazard regression analysis (1.48, 95% CI 1.19-1.76, p < 0.001). The authors identified an optimal cut-off value of 7.7 for MUC in predicting the risk of colectomy with an AUC of 83%, performing better than EMS (71%, p = 0.02) [40]. These results strengthen the feasibility of IUS tight monitoring in UC follow-up.…”
Section: Tight Monitoring In Uc: Preventing Colorectal Cancer (Crc) A...mentioning
confidence: 78%
See 4 more Smart Citations
“…Notably, MUC, over EMS and even BWT, was the only significant predictor of Cox proportional hazard regression analysis (1.48, 95% CI 1.19-1.76, p < 0.001). The authors identified an optimal cut-off value of 7.7 for MUC in predicting the risk of colectomy with an AUC of 83%, performing better than EMS (71%, p = 0.02) [40]. These results strengthen the feasibility of IUS tight monitoring in UC follow-up.…”
Section: Tight Monitoring In Uc: Preventing Colorectal Cancer (Crc) A...mentioning
confidence: 78%
“…In fact, the capability of safely and noninvasively predicting UC's long-standing course could potentially reduce hospitalizations, increasing surgical sparing and reducing the need for drastic rescue therapies. In this setting, the results of the studies by Piazza O. Sed and colleagues and Ilvemark and colleagues represented an innovative breakthrough in the understanding of IUS in UC [40,50]. The rectum is the main downside burdening IUS's role in UC management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations